UPAYA GURU PAI DALAM MENINGKATKAN RELIGIUSITAS PESERTA DIDIK - Aslamiyah, Siti Suwaibatul; Fitriyah, Aidatul (Akademika, 2018)
This study examines the efforts of PAI teachers in improving student religiosity. This study aims to determine the efforts of PAI teachers in improving student religiosity, supporting and inhibiting factors and giving solutions to overcome the inhibiting factors of PAI teachers in improving student religiosity. This study uses a qualitative research method through descriptive analysis. The results of the study could be concluded that there are some efforts made by PAI teachers in improving student religiosity including: providing guidance to all students to always worship and have morality, helping students with less religious knowledge, providing good examples for students, motivating students to actively perform worship and evaluate every activity. From the efforts made by PAI teachers, students coud be more diligent in conducting worship and having morality in accordance with the teachings of Islam. Supporting factors for teachers are internal factors, namely the teachers themselves; and external factors namely the existence of professional and qualified teachers who carry out their obligations properly, the existence of infrastructure supporting religious activities and the support from other teachers and all existing staff at school. Inhibiting factors for teachers include different student backgrounds and the environment or relationships that can affect students. The solution is to work with other teachers and students' parents so that they could supervise them.